(untitled) (Economics and region, 2019)
The contemporary approaches to the development of territories are considered in the article. It is noted that the integrated European approach to the development of territories is increasingly being applied in Ukraine. The essence of integrated development, the stages of development of the Integrated Development Strategy (Concept Strategy), emphasized that understanding of the role and functions of government and local self-government in the development and implementation of integrated development of territories should be perceived not only as the current management task, but also as social responsibility to the community and society. The key aspects of socially responsible behavior of authorities and local self-government in ensuring integrated development of territories are determined. It is noted that the perception of the fulfillment of its functions as social responsibility will allow to effectively plan and implement the development plans of the territories, compete for investments and the best jobs; use the local resource of the territory to create competitive advantages of the region, provide motivation and the ability of "key players" to use competitive advantages and to cooperate effectively; create and maintain institutions that promote the use of intellectual potential, ongoing modernization and innovation in the region; to ensure the willingness and ability of key institutions to adapt to the challenges of the global economy.